2023
DOI: 10.3390/s23031316
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Common Crucial Factors That Affect LoRaWAN Performance on Suburban and Rural Area Deployments

Abstract: LoRaWAN networks might be a technology that could facilitate extreme energy-efficient operation while offering great capacity for suburban and rural area deployment, but this can be a challenging task for a network administrator. Constraints that deform the trade-off triangle of coverage, scalability and energy efficiency need to be overcome. The scope of this study is to review the limitations of the LoRaWAN protocol in order to summarize and assess the crucial factors that affect communication performance, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In this study, we apply the Pareto front approach to the complex task of selecting optimal locations for multi-gateway deployment in large-scale LoRaWANs. Our objective is to achieve a harmonious equilibrium between minimizing overall costs and maximizing bitrate, as shown in Equation (17).…”
Section: Pareto Frontmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we apply the Pareto front approach to the complex task of selecting optimal locations for multi-gateway deployment in large-scale LoRaWANs. Our objective is to achieve a harmonious equilibrium between minimizing overall costs and maximizing bitrate, as shown in Equation (17).…”
Section: Pareto Frontmentioning
confidence: 99%
“…To formalize the problem, we utilize a general equation denoted as Equation (17), where the objective function f iq represents target i during the q sub-calculation. Specifically, for our endeavor in multi-gateway deployment in LoRaWANs, we adopt Equation (18) as the objective function.…”
Section: Pareto Frontmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have further demonstrated the performance and applicability of these technologies in different scenarios. For example, research conducted in [ 9 ] indicates the superior reliability of NB-IoT in mining environments near urban settings, while Ref. [ 10 ] highlights the cost-effectiveness of LoRaWAN in rural and suburban deployments.…”
Section: Introductionmentioning
confidence: 99%